1985
DOI: 10.1111/j.1365-2559.1985.tb02871.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonic mucosa adjacent to adenomas and hyperplastic polyps—a morphological and histochemical study

Abstract: The morphological and histochemical features of colonic mucosa adjacent to 142 adenomas and 31 hyperplastic polyps were studied. Three predominant patterns were identified: (1) normal mucosa, showing normal histological architecture and secretion of sulphomucins; (2) N+ type, histologically normal mucosa with predominance of sialomucins; (3) transitional mucosa; hyperplastic mucosa secreting sialomucins. Hyperplastic changes were observed in the immediate neighbourhood or at the base of adenomas and were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Hyperplasia is often accompanied by an increase in acidic mucins that have high levels of sialic acids (sialomucins) 27 , a trend also observed in this study ( Fig. 4 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hyperplasia is often accompanied by an increase in acidic mucins that have high levels of sialic acids (sialomucins) 27 , a trend also observed in this study ( Fig. 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…Mucins cover the entire colonic mucosa and changes in their expression and glycosylation are associated with progression to CRC 20 21 and can be associated with a poor prognosis 22 23 24 25 . Sialic acid content changes in colonic neoplasia 26 and hyperplastic tissue secretes mucus rich in sialomucins 27 . Therefore imaging agents that bind specific glycan moieties may be useful in distinguishing normal from dysplastic tissues as well as hyperplasia from dysplasia.…”
mentioning
confidence: 99%
“…[1][2][3] Several analyses concluded that this transitional mucosa contains more immature and intermediate cells and fewer differentiated cells and more sialomucin secretion than does nonhyperplastic normal mucosa, whose cells predominantly secrete sulfomucins. 4 -8 Whether the hyperplastic mucosa adjacent to colon cancer is a precancerous lesion 4,9,10 or a response to the growing cancer [11][12][13][14] or to microorganisms, such as Citrobacter freundii in humans 15,16 and Citrobacter rodentium in mice 17 has been debated. Hyperplasia of the ductal epithelium is often found adjacent to mammary adenocarcinoma and pancreatic cancer.…”
mentioning
confidence: 99%
“…These findings have suggested that the changes are a secondary phenomenon. It has also been pointed out that in certain instances, hyperplasia and mucin changes do not always occur together (Listinsky & Riddell 1981, Franzin et al 1983, Lanza et al 1985 and this further supports the concept that these changes are secondary.…”
Section: Discussionmentioning
confidence: 65%
“…This has not been reported. Secondly, a majority of adenocarcinomas and dysplastic foci in polyps actually secrete sulphomucins or show mixed secretion patterns as opposed to the abnormal sialomucins typical of transitional mucosa (Lanza et al 1985, Allen, Connolly & Biggart 1988. Allen and co-workers (1988) point out that this abnormal change to sialomucins in transitional mucosa and reversion to sulphomucins in dysplasia and carcinoma might be unusual for the proposed sequence of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%